A study on factor influencing the Hybrid Work culture for Middle Managers in Selected IT Website Development companies of Surat Region - Dr. Dhaval Hariyani (Journal of Informatics Education and Research, 2025)
The concept of 'hybrid work', characterised by the ongoing alternation between traditional and non-traditional work modes, has gained significant attention in recent research. Despite its growing relevance, a consistent and coherent conceptualisation of hybrid work remains elusive. This article aims to address this gap by providing a comprehensive and nuanced understanding of hybrid work, contributing to conceptual clarity in its application. The hybrid work culture influencing the job redesigning, job analysis, job classification & individual competency management & development. The application of redeveloping the improved write up on job description & specification, while using an expert system to educate and develop employee on advantages & disadvantages of hybrid work culture. We draw on an extensive literature in selected IT Services Sector companies on Surat Gujarat region.